Bechtel's BEMSIM Flowsheet Simulator Program for Commercial SX-EW Plant Design - Richard B. Stein (The Minerals, Metals and Materials Society, 1993)
Bechtel's BEMSIM computer program is a useful tool for solvent extraction-electrowinning plant design optimization. Its power (up to 90 stream components, 240 process streams, 180 process steps) has been applied to investigate floweheet configurations in order to perform basic engineering, sizing of plant equipment and to optimize performance of commercial-size copper plants. Flowsheet variations presented include series, parallel and series-parallel extraction stages, while heat balances simulate operations in summer and extreme winter conditions. The BEMSIM program has also been applied to nickel-cobalt, gold and manganese extraction.